Pengaruh Air Kelapa dan BAP terhadap Tanaman Teh Klon GMB 7 setelah Centering Ke-2 - HARJANTI, SYLVIA PUSPA; ROSNIAWATY, SANTI; ARIYANTI, MIRA; MAXISELLY, YUDITHIA (Agrotrop : Journal on Agriculture Science, 2019)
The Effect of Coconut Water and Bap on Tea Plant Clone Gmb 7 After 2 nd Centering . Tea plants as one of the leading commodities in Indonesia demanding high productivity. Clone GMB 7 and maintenance such as the formation of the area of plucking by 1 st centering and 2 nd centering on the immature plant can be done to improve the productivity of tea. Centering that plays a role in stimulating bud formation can be enhanced by the addition of Plant Growth Regulator (PGR) derived from natural ingredients such as coconut water and synthetic ingredients such as Benzyl Amino Purine (BAP). This research was conducted to determine the effect of BAP concentration and coconut water on tea plants after the 2 nd centering. The research was conducted from July 2017 to September 2017 at Ciparanje Field Station, Padjadjaran University. The experimental design used was Randomized Block Design with 7 treatments repeated 4 times. The treatment used were: control (without PGR); 25% coconut water; 50% coconut water; 75% coconut water; 60 ppm BAP; 90 ppm BAP; and 120 ppm BAP. The best result are shown by 50% coconut water on the ratio of leaves number, the ratio of bud number, and the bud length.